2001
DOI: 10.1111/j.1549-0831.2001.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Who's Afraid of the Big, Bad Wolf? Young People's Responses to the Conflicts Over Large Carnivores in Eastern Norway*

Abstract: Controversies over large carnivores are often interpreted as clashes between rural traditionalism and urban modernity. Rural communities, however, have never been culturally monolithic, and modernization will increase the diversity. To probe such diverse and changing attitudes towards nature, I conducted a qualitative study of young people in a rural community in eastern Norway. Contrary to popular images of such communities as unified against "pests," all typical views of the carnivore issue were present. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 20 publications
(23 reference statements)
4
72
0
3
Order By: Relevance
“…The arguments put forward by participants in this study closely resemble those reported from regions where large carnivores do exist, e.g. hunters' perception of being subject to the patronising attitudes of carnivore advocates (Skogen and Krange 2003), pride in being hunters and valuing their own practical knowledge above that of biologists or nature conservationists (Skogen 2001(Skogen , 2003 or the demand for population control through hunting (Sjölander-Lindqvist 2008, Liukkonen et al 2009). This suggests that social factors in conflicts about large carnivores operate somewhat independently from the animals.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The arguments put forward by participants in this study closely resemble those reported from regions where large carnivores do exist, e.g. hunters' perception of being subject to the patronising attitudes of carnivore advocates (Skogen and Krange 2003), pride in being hunters and valuing their own practical knowledge above that of biologists or nature conservationists (Skogen 2001(Skogen , 2003 or the demand for population control through hunting (Sjölander-Lindqvist 2008, Liukkonen et al 2009). This suggests that social factors in conflicts about large carnivores operate somewhat independently from the animals.…”
Section: Discussionsupporting
confidence: 62%
“…Several qualitative studies with this focus find that conflicts about large carnivores are a symptom of greater social conflicts, e.g. about different ideas on land use (Wilson 1997, Nie 2001, between different classes of society (Skogen 2001(Skogen , 2003, urban-rural tensions and different forms of knowledge Krange 2003, Sjölander-Lindqvist 2008) or opposition to nature conservation associations and policies (Skogen et al 2008, Liukkonen et al 2009). …”
mentioning
confidence: 99%
“…Hence, centralized carnivore management may be considered as a more provocative policy among Norwegians than Swedes, motivating rebellion against central authorities (Muth & Bowe 1998), and leading to Norwegians being more accepting of and willing to commit illegal hunting (Otterlei & Sande 2010;Krange et al 2012). For example, rural men with strong hunting traditions resist carnivore re-establishment, especially the wolf, as an act of cultural or social protest (Skogen 2001(Skogen , 2003Skogen & Thrane 2008). Kaltenborn et al (1998) used the NEP scale to look at how attitudes toward predators were reflected by environmental value orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Such methods do not, however, tend to be able to fully explain the complex phenomena surrounding the 'how's and 'why's of human behaviour, particularly those related to culture (Skogen, 2009). Qualitative methods can therefore play a significant role in unravelling the underlying drivers of why conflict has not been mitigated.…”
Section: The Human Dimensions Of Global Carnivore Conservationmentioning
confidence: 99%
“…Qualitative methods are especially useful in uncovering unexpected results that can help to paint rich picture of why and how 2 One notable researcher who is an exception to this rule is Ketil Skogen and colleagues, who have published quite extensive qualitative studies on this topic in Scandinavia (e.g. Skogen & Krange, 2003;Skogen, Mauz, & Krange, 2008;Skogen, 2009Skogen, , 2010. However, limited in-depth qualitative work has been conducted outside of this geographic area.…”
Section: The Human Dimensions Of Global Carnivore Conservationmentioning
confidence: 99%